Fenugreek extract as a natural therapy for dyslipidaemia: an in vivo study on rats - Jawad, Dhafer; Khalifa, Abdulrhman Y.; Mones, Mawahb Hatem; Abed, Hayder H. (Pharmakeftiki, 2025)
Dyslipidaemia is a major risk factor for cardiovascular disease, necessitating effective lipid-lowering interventions. This study investigates the lipid-modulating effects of fenugreek (Trigonella foenum-graecum) extract in comparison to atorvastatin, on rats, with a focus on dose-dependent responses. Male rats (n=150) were randomly assigned to five groups (n=30 per group): negative control (NC), positive control treated with atorvastatin (5–20 mg/kg), and three experimental groups receiving low (100 mg/kg), medium (250 mg/kg), or high (500 mg/kg) doses of fenugreek extract. Lipid profiles – including total cholesterol (TC), low-density lipoprotein (LDL)-cholesterol, high-density lipoprotein (HDL)-cholesterol, and triglycerides (TG) – were assessed post-treatment using standard biochemical assays. Atorvastatin significantly reduced TC (75.33 ± 19.49 mg/dL, p<0.05) and LDL-cholesterol (26.93 ± 10.36 mg/dL, p<0.0001), while elevating HDL-cholesterol (55.20 ± 13.19 mg/dL, p<0.0001). Similarly, high-dose fenugreek extract significantly lowered TC (75.97 ± 32.58 mg/dL, p<0.05) and LDL-cholesterol (22.17 ± 10.11 mg/dL, p<0.0001), with a concomitant increase in HDL-cholesterol (57.90 ± 20.45 mg/dL, p<0.0001). No significant changes in TG levels were observed across the assessed groups. These findings suggest that the fenugreek extract, particularly at higher doses, exerts lipid-lowering effects comparable to atorvastatin, supporting its potential as a natural alternative or adjunctive therapy in the management of dyslipidaemia.